Applying Artificial Intelligence in Supply Chain Management - Alfawaz, Khaled Mofawiz; Alshehri, Ali Abdullah (Communications in Mathematics and Applications, 2022)
With the international scale context this study, it gives a top level view of the idea of AI pushed supply chain studies, the rising AI primarily based totally enterprise fashions of various case businesses are analysed. Maintainable overall performance and flexibility occupy a huge a part of the charities and studies works associated with the supply chain and logistics, on the only hand due to the dangers innate with inside the supply chain and the opposite hand due to outside turbulences, dangers and crises that may briefly or robustly effect customer’s service. Some of the overall performance matrices which includes advertising and marketing techniques of SCM, want destiny amendment of SCM, function of Artificial Intelligence in SCM production, improvement of SCM is the manner to get achievement for the retail production, function of Artificial Intelligence with inside the organization, key reason of Artificial Intelligence and Purpose of SCM with inside the organization need to be taken in count. Along with those overall performance metrics will support to beautify the deliver chain control functionalities which cause enhance the enterprise.